A review of electric vehicle charging management based on the communication between EV, RSU and CS - Mohammed D.; Mansor M.B.; Hock G.C. (American Institute of Physics Inc., 2024)
Developed countries continue to search for solutions to reduce carbon emissions and increase energy efficiency. Therefore, developed countries have adopted EVs and have integrated them into smart transportation systems (ITS). Electric vehicles (EV) equipped with communication devices and wireless sensors such as an onboard unit (OBU) allow wireless communication between electric vehicles (EV) and roadside units (RSU) called V2I and between electric vehicles and smart grid components such as charging stations (CS) called V2G. This paper reviews EV charging management in terms of the different types of messages that are exchanged between V2I and V2G by the IEC 61850 and IEEE WAVE standards. Besides, this paper explains the algorithm used to schedule electric vehicle charging based on the connection between V2I and V2G. This algorithm ensures that the needs of electric vehicles are met by supplying them with energy through information obtained between the electric vehicle, RSU, and CS. The accurate information obtained through this communication system enables the EV owners to estimate the distance to the nearest and available charging station that may accept EV without burdening the distribution networks. This research will help to give an overview for researchers about the electrical vehicle charging systems. 2023 Author(s).